Testing Kuznets curve hypothesis for the relationship between economic growth and environmental pollution in Sudan during the period 2000-2022 - Jaralnab, Jaralnabi Babou; Ahmed, Salma NourAlHuda; Hapallah, Safia Omer (Journal of Economic, Administrative and Legal Sciences, 2025)
The study attempted to test the Kuznets curve hypothesis for the relationship between economic growth and environmental pollution in Sudan during the period (2000-2022), and to verify the extent to which the environmental Kuznets curve hypothesis was achieved, it used the autoregression distributed lags method, and its results revealed existence of appositive relationship between economic growth and environmental pollution in the short and long run, and the positive relationship in the long run contradicts the hypothesis of the study, which means that the high growth rate of the Sudan's economy does not lead to improving environment level, and there is appositive relationship between population and environmental pollution, which indicates to un optimal use of environmental resources as a result of poor population distribution and overcrowding in cities. It recommended paying attention to the environment as the sustainable development variables by directing research and development expenditure to environmental quality projects, activating environmental protection laws that guarantee the rights of future generations, and reducing the increase in population density in capital and some parts of the country Cities through optimal distribution of development projects.
Keywords: Economic growth; Kuznets curve; environmental pollution; ARDL; population